Preliminary Investigation of the Psychometric Properties of the Parent Version of the Borderline Personality Features Scale for Children (BPFS-P). Issue 5 (3rd September 2021) - Babinski, Dara E.; Castagna, Peter J.; Waschbusch, Daniel A.
Abstract: There is growing evidence that features of borderline personality disorder (BPD) emerge in childhood and present long-term risk for the development of BPD. Thus, valid and reliable assessments of BPD features in childhood are needed. This study examined the psychometric properties of the parent version of the Borderline Personality Features Scale for Children (BPFS-P) in a large, representative sample ( N = 1, 050; 51.5% male; M age = 8.42, SD = 2.31; Agerange = 5 to 12 years). The factor structure of the BPFS-P was examined, and measurement invariance was tested across child age and sex as well as caregiver informant sex. Additionally, the unique contribution of the identified factors of the BPFS-P to overall impairment and need for treatment beyond co-occurring dimensions of additional psychopathology was examined. A one factor structure was identified, which demonstrated measurement invariance across child sex and age as well as caregiver informant sex. BPD features measured with the BPFS-P contributed unique variance to explaining overall impairment and need for treatment. These findings point to the potential of the BPFS-P to break new ground in identifying youth at risk for BPD.